Listeria monocytogenes in Ready-to-Eat Seafood and Potential Hazards for the Consumers. (16th June 2012) - Gambarin, Patrizia; Magnabosco, Cristian; Losio, Marina Nadia; Pavoni, Enrico; Gattuso, Antonietta; Arcangeli, Giuseppe; Favretti, Michela
Abstract : The risk of exposure to Listeria monocytogenes ( L. monocytogenes ) when consuming Ready-to-Eat (RTE) seafood was assessed in the Veneto Region (Italy). Thirty-eight samples were analyzed, each sample consisted of three subunits belonging to the same batches. The first of the three units was examined immediately, the second was stored at +4°C (for all of its shelf-life) and the third at +10°C (for the latter third of its shelf-life ) before the analysis. Chemical-physical and microbiological parameters were tested simultaneously. Culture results showed the presence of viable L. monocytogenes in 9 (23, 68%) of the 38 samples analysed, 3 (33, 33%) of which with a concentration >100 cfu/g. PCR tests yielded 12 L. monocytogenes positive samples. Semipreserves with aw (water activity) and pH values that favour L. monocytogenes growth were the only ones to result positive to microbiological and PCR tests. Temperature proved to be an important factor as it limits the growth of L. monocytogenes, including products with potentially high competitive microbial charges. Four different serotypes were recovered and ribotyping has helped to highlight the genomic variability of L. monocytogenes strains in food. This supports the hypothesis that L. monocytogenes continues to evolve genetically to the detriment of phenotypic conservation.